Efficacy of a school based intervention plan for victims of bullying / Umaimah Maryam and Tazvin Ijaz - Maryam, Umaimah; Ijaz, Tazvin (2018)
Bullying has become a common problem for today's youth, compelling researchers and policymakers to focus their attention towards addressing this issue in schools. This study aimed at devising a holistic plan to curb bullying by improving the pro-social behaviour of bullied schoolchildren, helping them avoid bullying, evade its adverse effects and helping the school make policy changes. A school-wide intervention plan was created for Pakistani schools. Two schools were involved in the study, one control and one experimental. 12 victims were recruited for this study, six from each school. The victims were selected through teacher reports and were later screened for bullying using Illinois Bully Scale (IBS). The same scale was used to study bullying, victimisation and fighting tendency of the participants, and to evaluate their social skills, How Are My Social Skills Checklist (SSC) was used. The study and the intervention, each had three phases. Study: pre-assessment, intervention and post-assessment. Intervention: individual and group therapy (emotional management, social-skill building and problem-solving), teacher and parent training, and anti-bullying school-policy. Pre-post IBS and SSC scores revealed significant improvement in the experimental group.